2018
DOI: 10.1186/s12909-018-1189-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrating student feedback during “Dental Curriculum Hack-A-thon”

Abstract: BackgroundThe future of dental education is at crossroads. This study used the parameter of the 2016 Dental Curriculum Hack-a-Thon to assess intra- and inter-institutional agreement between student and faculty views regarding dental curriculums to determine if there is an impact in student perceptions towards dental education from before and after the event.MethodsThis exploratory, cross-sectional study involved two surveys, with Survey 1 being distributed among four faculty-student pairs of the four participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…In addition, the value of integrating student feedback in shaping the curriculum and their unique perspectives have been previously reported in dental education. 19,20 Future studies are recommended that will include direct comparison among perceptions from the students, staff, faculty and administrators on the transition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the value of integrating student feedback in shaping the curriculum and their unique perspectives have been previously reported in dental education. 19,20 Future studies are recommended that will include direct comparison among perceptions from the students, staff, faculty and administrators on the transition.…”
Section: Discussionmentioning
confidence: 99%
“…CBL was shown to be effective in enhancing the knowledge of dental interns. Saffari et al 27 assessed whether there was agreement between the views of students and faculty concerning dental curricula and twenty‐eight dental students participated. These studies indicated the importance of obtaining students’ views on the designing of the curriculum and on the deliverance of their education.…”
Section: Discussionmentioning
confidence: 99%
“…Gies (13) emphasized the initial necessity for curriculum modi cation in dentistry schools to "progress instruction". Furthermore, a range of scienti c research (14)(15)(16)(17) has underlined the need for a pedagogical shift in dentistry education toward a more technologically based curriculum. The academic institutions themselves are seen to be driving this broad interest in curriculum change to increase the quality of oral health instruction for dentistry students.…”
Section: Discussionmentioning
confidence: 99%